2019
DOI: 10.1177/0271678x19825785
|View full text |Cite
|
Sign up to set email alerts
|

Fracture shortly before stroke in mice leads to hippocampus inflammation and long-lasting memory dysfunction

Abstract: Cognitive impairment occurs in stroke and hip fracture patients. In mice, bone fracture (BF) exacerbates stroke-related neuronal damage and sensorimotor dysfunction. We hypothesize that BF exacerbates post-stroke cognitive impairment. Adult mice were randomly assigned into BF, stroke, BF+stroke (BF 6 h before stroke), and control (sham operated) groups. Memory function was evaluated weekly for eight weeks by Y maze test and at eight weeks post-surgeries by novel object recognition (NOR) test. The neuronal dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Furthermore, BF reduced WM in the basal ganglia and enhanced WM damage in the basal ganglia of the stroke mice. All of this could contribute to the previously observed long-lasting memory dysfunction of BF+stroke mice [ 32 ].…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Furthermore, BF reduced WM in the basal ganglia and enhanced WM damage in the basal ganglia of the stroke mice. All of this could contribute to the previously observed long-lasting memory dysfunction of BF+stroke mice [ 32 ].…”
Section: Discussionmentioning
confidence: 95%
“…Our team reported previously that BF occurring 6 h or 24 h before or 24 h after stroke exacerbated neuroinflammation, brain edema and neuronal damage in the infarct and peri-infarct regions, and enhanced sensorimotor dysfunction of the stroke mice [ 13 , 14 , 15 , 16 , 41 ]. Our team had also shown that BF occurring 6 h before stroke led to long-lasting memory impairment (>8 weeks) of young mice [ 32 ]. Clinically, patients with stroke plus BF need more care and have poorer recovery than those with stroke alone [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations